The roles of information and communication technologies, green innovation, and globalization in driving carbon emissions in g-20 countries - Yap, Le Ting (2023)
To combat global climate change, it is necessary for all nations to make collective efforts towards integrated, sustainable, and innovative technologies. This study intends to investigate the roles of Information and Communication Technologies (ICT), green innovation and globalization on carbon dioxide (CO2) emissions in G20 countries by employing a quantile regression analysis. The research also explores the existence of the Environmental Kuznets Curve (EKC) in these countries. The results suggest that the effects of ICT, green innovation, and globalization vary depending on the level of carbon dioxide emissions. Even though the findings indicate ICT and green innovation exacerbated CO2 emissions in the lower CO2 emissions countries and in the majority of G20 countries respectively, the globalization was found to reduce the CO2 emissions in high CO2 emissions countries. As for the EKC hypothesis, it is found to be valid for ICT in low carbon emissions countries, green innovation in medium to high carbon emissions countries, and globalization in high carbon emissions countries. The outcomes of this research could assist policymakers in better understanding the factors driving CO2 emissions and the potential for ICT, green innovation, and globalization to mitigate air pollution in BRI countries.